Examination of Lower Passing Ability of Class VIII SMP Negeri 1 Bangkala Kab. Jeneponto - Amirah, Nur fadilah; Basram, Nafi; Hakim, Hikmad; erfanda, Poppy Elisano; Hudain, Muh Adnan Elisano (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives Examination of the Subpar Passing Capability of Eighth Grade Students at SMPN 1 Bangkala. Dissertation. Department of Health and Recreation Physical Education, Faculty of Sports Science. Materials and Methods Makassar State University (Under the guidance of Irva and Sufitriyono) This study employs a quantitative descriptive approach. The participants in the investigation were eighth-grade students at SMPN 1 Bangkala. The study was carried out on July 29, 2023. The instruments utilized for the study included (1) an Ability Test and (2) Documentation. Data processing involves the application of descriptive statistics, whereas analysis techniques employ percentages. Results. The findings regarding the passing abilities of class VIII students at Bangkala 1 Public Middle School indicate that in the "Very Good" category, there was 1 student, representing 3.3%. In the "Good" category, there were 10 students, accounting for 33.3%. The "Medium" category included 12 students, or 40%. In the "Less" category, there were 4 students, which is 13.3%, and additionally, 3 students also fell into the "Less" category. Conclusions. The findings indicate that the passing ability of class VIII students at SMP Negeri 1 Bangkala is categorized as "Medium."